Catalytic Sonolysis Of Used Motor Oil - Mohamed Rosli, Ahmad Zaki (Universiti Sains Malaysia, 2018)
Motor oil is used as lubricant for various types of mechanical contraption in industry and in our daily life which its purpose is to protect the equipment, ensure that it operates in a correct manner and lengthen its lifetime. Since it was used widely, its disposal method become an issue as the used motor oil is hydrocarbon that need to be disposed properly in order to protect the environment. Therefore recycling of used motor oil can reduce the disposal. The motor oil contains heavy portion that can be cracked into lighter oil and can be used as fuel for heating purposes. The used motor oil usually has high viscosity that make the transportation process difficult. Ultrasonic treatment is used in the present study to crack the heavier hydrocarbon in the used motor oil and to reduce the viscosity. Cobalt and nickel are commonly used catalysts in the petroleum industry and their effect on the cracking of used motor oil using ultrasonic treatment are investigated. In this research different parameters such as amplitude of the ultrasonic, residence time, catalyst amount and catalyst type were studied to determine the sonocracking effect to the used motor oil. Through this experiment, the result showed that the used parameter range (20%-60% amplitude, 5-30 minutes residence time) and catalyst type (Co/HZSM-5 and NiCo/HZSM-5)increased the viscosity of the used motor oil from the initial of 116.7cP to 179.23cP in no catalyst condition, 60% amplitude and 25 minutes residence time. In this condition, the residue percentage reduced from 64% to 51%. As for the other experiments, the residue content increased. To obtain the desired result, different parameters study range and catalyst type could be investigated.